UNDERSTANDING AND APPLICATION OF GREEN ACCOUNTING COFFEE SHOP KEDUNG BARUK URBAN VILLAGE - Novita Rahmawati; Maria Yovita R Pandin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the level of understanding and application of the will of cloning in coffee shops in Kedung baruk village. Green accounting is an accounting method that correlates environmental aspects and sustainability regarding the measurement of reporting and financial analysis of an organization aims to integrate environmental and social information into the financial statements of the decision-making process that allows a more comprehensive assessment of social and environmental financial performance. Techniques using observation questionnaires, interviews, documentation to bury research data. Data analysis in conducting this research is descriptive qualitative. The results of this study are that the coffee shop actors in the new building understand the earthquake and apply it in their operational activities and understand the importance of considering the environmental impact of the coffee shop business taking steps to reduce negative impacts by reducing negative impacts in making handicrafts to protect the environment and there are still some Warkop who do not understand and apply it in their operations. In the way of providing environmental accountability that has gone through the stage of adjustment with various environmental objectives and corporate ideals, environmental costs can be in the form of costs of steps taken, or that must be taken to regulate various environmental impacts on company activities.